UN MILLENNIUM DEVELOPMENT GOALS INDICATORS ON PROBLEMS OF ACCESS TO ESSENTIAL MEDICINES AND ENHANCEMENT OF LOCAL PHARMACEUTICAL PRODUCER IN DEVELOPING COUNTRIES - A. Y. Kulikov; A. G. Voskanyan (Фармакоэкономика, 2015)
The article covers the key issues of local pharmaceutical production and ensuring of equitable access to essential medicines in the scopes of the UN «Millennium Development Goals». In particular, it presents the main activities of UN agencies, as well as the World Health Organization projects aimed at realization of human rights to health and development.